Securities law - Nicholls, Christopher C. (Essentials of Canadian law, 2023)
"Canadian securities law consists of an enduring core of fundamental principles that are refined, and sometimes shrouded, by a complex and constantly evolving body of technical details. This third edition, written by Christopher Nicholls — one of Canada’s foremost corporate and securities law experts — provides a solid grounding in the core securities law principles and helps the reader navigate the complex labyrinth of modern securities regulation. Securities Law surveys the essential building blocks of securities regulation: basic definitions, the public and exempt markets for securities, insider trading, continuous disclosure, enforcement, regulation of dealers and other securities industry professionals, and take-over and issuer bids. Discussion of these subjects is interwoven with thoughtful consideration of larger public policy issues. This book also explores the history of securities regulation and several recent topics, including, among others, the stalled initiatives aimed at trying to create a national cooperative capital market regulatory system in Canada; developments affecting dealers including the recent proposed consolidation of Canada’s two national securities industry self-regulatory organizations; impact of the 2021 Capital Markets Modernization Taskforce Report; changes introduced in Ontario by the Securities Commission Act, 2021; and the ongoing challenges posed by increasing shareholder activism and technological advances, including the regulatory challenges posed by cryptocurrencies and other digital assets."-- Provided by publisher.